ChemInform Abstract: An Efficient and Highly Stereoselective Approach to trans‐2, 5‐Disubstituted‐tetrahydrofuran and trans‐2, 6‐Disubstituted‐tetrahydropyran Derivatives. Issue 47 (6th November 2014) - Veidenberg, Indrek; Toom, Lauri; Villo, Piret; Vares, Lauri
Abstract Kinetic resolution of bis‐epoxides followed by cyclization allows the synthesis of tetrahydrofuran and pyran derivatives in an enantio‐ and diastereoselective manner.